2003
DOI: 10.1046/j.1365-2133.2003.05377.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-associated retinopathy: high frequency of subclinical findings in patients with melanoma

Abstract: Subclinical retinal involvement characteristic of MAR appears to be more common than previously suspected in patients with cutaneous malignant melanoma. Our findings in this small cohort seem to indicate that the percentage of patients with symptoms suggestive of MAR is higher in advanced stages of disease. Further clinical studies are required to evaluate if the presence of subclinical symptoms suggestive of MAR is correlated with a worse prognosis and a shortened progression-free and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 18 publications
(19 reference statements)
3
18
0
2
Order By: Relevance
“…The main clinical symptom is a sudden loss of vision or visual photopsias. Pföhler et al [7] reported a case series of patients with subclinical findings or asymptomatic MAR suggesting that MAR is probably underdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main clinical symptom is a sudden loss of vision or visual photopsias. Pföhler et al [7] reported a case series of patients with subclinical findings or asymptomatic MAR suggesting that MAR is probably underdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…These antiretinal antibodies are also present in many ocular diseases and other paraneoplastic retinopathies. Therefore, the presence of these autoantibodies is not sufficient to diagnose MAR, and clinical ophthalmologic symptoms have to be present, although they are sometimes very mild (night blindness, light sensations) [7,14]. The prognostic relevance of antiretinal antibodies has not been evaluated, and it is not known if their presence changes the course of melanoma [14].…”
Section: Discussionmentioning
confidence: 99%
“…In our patient with no antiretinal antibodies and a normal ERG, MAR syndrome is unlikely. 6 The vitelliform lesions of our patient may resemble other disorders with vitelliform lesions like acute exudative polymorphous vitelliform maculopathy 7 (AEPVM) or adult vitelliform macular dystrophy 8 (AVMD). Both diseases show normal ERG and no antiretinal antibodies.…”
Section: Commentmentioning
confidence: 80%
“…Thus, retinal degeneration may be a frequent symptom in melanoma patients remaining, however, at a subclinical level. Pf€ ohler et al 31 have shown that these subclinical manifestations of MAR are more frequent in advance stages of melanoma. Therefore, an ophthalmological examination may not be suitable for an early melanoma diagnosis, although this needs to be tested by further clinical studies in melanoma patients and/or in mice during melanoma development.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been published that subclinical manifestations of MAR may appear more often than previously suspected in melanoma patients. 31 The authors have investigated about 30 patients with malignant melanoma by ERG, static and kinetic perimetry, and nyctometry. Subclinical MAR symptoms were found in 90% of the patients.…”
Section: Discussionmentioning
confidence: 99%